Rorokan Adat Struktur Kemasyarakatan Tradisional di Kasepuhan Ciptagelar Kabupaten Sukabumi (Kajian Etnografi) - ELVA YULIA SAFITRI; DEDE KOSASIH; DIAN HENDRAYANA (JALADRI : Jurnal Ilmiah Program Studi Bahasa Sunda, 2024)
The background of the research was carried out due to the lack of social knowledge about the traditional social system that is still carried out in the lives of indigenous peoples. The purpose of this study are to describe 1) the history of Kasepuhan Ciptagelar, 2) the role and function of the elders of Kasepuhan as well as the traditional customs or social system in Kasepuhan Ciptagelar, and 3) the governance of Kasepuhan Ciptagelar. The research method used is descriptive qualitative-participant method, by using an ethnographic understanding that has the purpose of circumstance research, by participating into the lives of the people researched. The techniques used are participatory observation techniques, interviews, and documentation.